The EuroQol Group after 25 years - Brooks, Richard; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The EuroQol Group first met in Rotterdam in May 1987 determined to develop a standardised non-disease-specific instrument for valuing health-related quality of life. The book traces the activities of the Group over the next 25 years. The instrument constructed, eventually named the EQ-5D, was translated into many languages and used in a wide range of countries and settings. The book describes how the instrument$1 (Bs descriptive system was determined, how translation and language issues were handled, and how valuations were provided. Recent developments, in particular a 5-level version (EQ-5D-5L), and a youth version (EQ-5D-Y) are covered. The history of the institutional and administrative framework within which the Group operated is also treated.s
Preface -- 1 Introduction -- 2 The early years -- 3 Descriptive system -- 4 Translation, language and semantic issues -- 5 Valuation -- 6 Applications -- 7 EuroQol organisation and administration -- 8 Research, product development and the work of the Task Forces -- 9 The future -- References -- Appendices -- Index.
Keywords: Medicine; Quality of Life; Quality of Life -- Research; Biomedicine; Biomedicine general; Quality of Life Research